REPRESENTASI MOTIVASI MAHASISWA MEMILIH KULIAH DI SEKOLAH TINGGI PASTORAL ATMA REKSA (STIPAR) ENDE - Age, Maria Yulita C. (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This study aims to describe the motivation of students to choose to study at Stipar Ende. The method used in this study is a descriptive survey. Determination of the sample was carried out by purposive sampling technique (purposive sampling). The sample in this study were all Stipar Ende students (semester I), totaling 165 people. The variable of this research is the motivation to choose to study at Stipar Ende, which consists of intrinsic motivation and extrinsic motivation. Data collection techniques were carried out using scaleless questionnaires which would be converted into numbers so that they could be analyzed statistically and structured interviews were conducted to test the credibility of the research. The data analysis technique in this study is percentage analysis. The results showed that students' intrinsic motivation in choosing to study at Stipar Ende was dominated by the dream of becoming a Catholic religion teacher or catechist, amounting to 33.96%. Meanwhile, extrinsic motivation was dominated by parents' willingness to have their children study at Stipar Ende by 11.32%.